2019
DOI: 10.3151/jact.17.405
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-Based Modeling for Water Permeability of Hydrating Cement Paste

Abstract: Water permeability is a key property for the serviceability and durability of concrete structures, which governs the transport of fluid through the pore network in the cementitious material. A microstructure-based numerical test method is proposed and employed to predict the permeability of hydrating cement paste. Numerical samples characterizing the evolution of the microstructure of cement paste are generated using the computational code HYMOSTRUC3D. Based on the three-dimensional (3D) finite element method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The main purpose of this study is to obtain the 3D pore network using the MCP method for predictions of transport properties and understand the Fig. 8(a) shows the simulated ionic diffusivity and water permeability in cement paste with w/c ratios of 0.5, 0.6 and 1.0, in comparison with experimental data obtained from literature (Care 2008;Grasley et al 2007;Hamami et al 2012;Li et al 2016;Li and Xu 2019;Ngala et al 1995;Numata et al 1990;Phung et al 2013;Poupard et al 2004;Rose and Grasley 2017;Tracz 2016;Zheng et al 2018). Generally, the ionic diffusivity of cement paste is measured through chloride diffusion using the spectrophotometric technique (Ngala et al 1995), colourimetric method (Care 2008), and electrical field acceleration method (Zheng et al 2018;Poupard et al 2004), while fluid permeability are referred to water permeability and gas permeability measured using dynamic pressurization technique (Grasley et al 2007;Rose and Grasley 2017;), pressure-induced method (Hamami et al 2012;Li and Xu 2019;Hamami et al 2012), and constant water-flow method (Phung et al 2013).…”
Section: Simulation Results Of Transport Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main purpose of this study is to obtain the 3D pore network using the MCP method for predictions of transport properties and understand the Fig. 8(a) shows the simulated ionic diffusivity and water permeability in cement paste with w/c ratios of 0.5, 0.6 and 1.0, in comparison with experimental data obtained from literature (Care 2008;Grasley et al 2007;Hamami et al 2012;Li et al 2016;Li and Xu 2019;Ngala et al 1995;Numata et al 1990;Phung et al 2013;Poupard et al 2004;Rose and Grasley 2017;Tracz 2016;Zheng et al 2018). Generally, the ionic diffusivity of cement paste is measured through chloride diffusion using the spectrophotometric technique (Ngala et al 1995), colourimetric method (Care 2008), and electrical field acceleration method (Zheng et al 2018;Poupard et al 2004), while fluid permeability are referred to water permeability and gas permeability measured using dynamic pressurization technique (Grasley et al 2007;Rose and Grasley 2017;), pressure-induced method (Hamami et al 2012;Li and Xu 2019;Hamami et al 2012), and constant water-flow method (Phung et al 2013).…”
Section: Simulation Results Of Transport Propertiesmentioning
confidence: 99%
“…18 (Care 2008;Grasley et al 2007;Hamami et al 2012;Li et al 2016;Li and Xu 2019;Ngala et al 1995;Numata et al 1990;Phung et al 2013;Poupard et al 2004;Rose and Grasley 2017;Tracz 2016;Zheng et al 2018).…”
Section: Simulation Results Of Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of nuclear power plants, capturing the temperature dependency of this dynamic microstructure (related data has been reported by ) is critical for a more accurate estimation of the moisture transport, such as in a recent trial by Li and Xu (2019). To the authors' knowledge, no similar data for mid-range periods have been reported thus far.…”
Section: Introductionmentioning
confidence: 90%
“…In the context of nuclear power plants, capturing the temperature dependency of this dynamic microstructure (related data has been reported by Maruyama and Rymeš (2019)) is critical for a more accurate estimation of the moisture transport, such as in a recent trial by Li and Xu (2019). To the authors' knowledge, no similar data for mid-range periods have been reported thus far.…”
Section: Introductionmentioning
confidence: 90%